The Influence of Safety Management Practices On Safety Behavior: A Study Among Manufacturing SMES In Malaysia - Chandrakantan Subramaniam; Zuraida Hassana; Md. Lazim Mohd. Zin; Subaramaniam Sri Ramalu; Faridahwati Mohd. Shamsudin (International Journal of Supply Chain Management, 2016)
Safety at work is one of the key issues in many organizations. This is because accidents and injuries in the workplace can cost the organization financially and non-financially. Although workplace safety has been widely investigated, less attention is given to the small and medium enterprises. Such neglect is unfortunate because many accidents and injuries around the world, including Malaysia, happen in this organizational milieu. A survey of 74 employees of SMEs in the northern region of Peninsular Malaysia was carried out. Self-reported measures were used to obtain data on workplace safety dimensions and safety behavior. The Partial Least Square (PLS) structural model analysis was used to ascertain the proposed relationships. The present study found that only three dimensions of safety management practices (management commitment, safety training, and safety rules and procedures) were significantly related to safety behavior. Implications for managers and practitioners are discussed.